Peran Bahasa Gaul dalam Membentuk Identitas dan Penerimaan Sosial Generasi Muda - Abigail Miracle; Nadia Rifanti; Tio Indra Gunawan; Titan Agestin; Achmad Hufad; Yani Achdiani (Jurnal Konseling dan Psikologi Indonesia, 2026)
This study aims to examine the role of slang language in shaping the identity and social acceptance of young people in the digital era. Slang, which has developed rapidly through social media, is not only used as a means of communication but has also become part of how young people express themselves, build social closeness, and demonstrate group identity. This study employed a qualitative method with a descriptive-analytical approach. Data were collected through interviews and observations involving university students and several representatives of older generations within the campus environment. The findings indicate that the use of slang can strengthen social relationships, foster a sense of belonging, and facilitate individuals’ acceptance within friendship groups. In addition, slang functions as a medium of self-expression and a symbol of an individual’s engagement with the development of digital culture. Social media platforms such as TikTok, Instagram, and X were found to be the primary factors driving the spread of slang vocabulary among young people. The novelty of this study lies in its discussion of the relationship between slang, social identity formation, and social acceptance through the perspective of symbolic interactionism in the context of digital communication. The findings contribute to the field of social psychology by demonstrating that language plays an important role in the processes of identity formation, social interaction, and individual acceptance within modern society.